2020
DOI: 10.1108/srj-03-2019-0108
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing sustainability in the contemporary model of CSR: a case of fast fashion industry in developing countries

Abstract: Purpose This study aims to point out the importance and the relevance of sustainability issues and the need for their enhancement in the contemporary model of corporate social responsibility (CSR) as the top priority for business entities. Furthermore, it also highlights ways to enhance sustainability in the contemporary CSR model in the fast fashion industry of developing countries. Design/methodology/approach Literature review has been extensively done through available databases, including ProQuest and Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 47 publications
4
29
0
3
Order By: Relevance
“…This finding is rather disappointing, keeping in view the poor climatic conditions of Pakistan, because small-sized enterprises in Pakistan exist in large numbers, and if such a large number are neglecting the environment, then it will be very difficult for the country to hope for a better and sustainable future. There are studies in the extant literature that also confirmed that environmental improvement through CSR is something that is not the priority of most developing countries in the world [73,74]. These results are dissimilar with the studies in developed countries, where many of steps have been taken to improve the environmental footprint of the enterprises through CSR [75,76].…”
Section: Discussionmentioning
confidence: 89%
“…This finding is rather disappointing, keeping in view the poor climatic conditions of Pakistan, because small-sized enterprises in Pakistan exist in large numbers, and if such a large number are neglecting the environment, then it will be very difficult for the country to hope for a better and sustainable future. There are studies in the extant literature that also confirmed that environmental improvement through CSR is something that is not the priority of most developing countries in the world [73,74]. These results are dissimilar with the studies in developed countries, where many of steps have been taken to improve the environmental footprint of the enterprises through CSR [75,76].…”
Section: Discussionmentioning
confidence: 89%
“…When the leadership is developing a good strategy for sustainable development, a consistent commitment to sustainability within the organization is required (Lee and Schaltegger, 2014 ). Leadership plays an important role in promoting CSR (Fenwick, 2007 ; Mayo et al, 2016 ; Mallén Broch et al, 2020 ; Nguyen et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…CSR has played a very crucial role in bridging the gap between the governments and companies in the developed economies. However, developing countries are practicing CSR mainly in a voluntary and philanthropic fashion to build public image and primarily enhance business profit, not necessarily for social well-being and environmental benefit (Nguyen et al , 2021).…”
Section: Discussion and Recommendationmentioning
confidence: 99%